PRAKTIK MEMANCING DI JERMAN: KEGEMARAN DAN TANGGUNG JAWAB - Rachman, Adelia; Setiadi, Setiadi (Paradigma: Jurnal Kajian Budaya, 2025)
Angling has been taking place and is deeply rooted in historically German culture. Its functionality evolves from subsistence, economic livelihoods, customs and traditions, to recreational activities offering enjoyment of nature. Summer field research was conducted around Baden-Württemberg and Hessen with ten anglers of diverse backgrounds living in Germany. The qualitative ethnographic research and perspective-taking approach were applied through participant observation, in-depth interviews, and literature studies to explore the current angling culture in freshwater ecosystem landscapes comprising angling experiences and practices, and anglers’ perceptions. The research findings demonstrate angling goes beyond fondness, it is a matter of responsibility in terms of animal welfare and ecosystem balance as is evident from anglers’ ecological consciousness adhering to the fishing rules and procedures, besides ethical considerations of human-nonhuman relations. Understanding fish through othering does not necessarily signify human supremacy over other species, but rather an act of reconciling, considering biological differences are ineluctable features of biological systems.